Increase in the Thermic Effect of Food in Women by Adrenergic Amines Extracted from Citrus Aurantium - Gougeon, Réjeanne; Harrigan, Kathy; Tremblay, Jean-François; Hedrei, Philip; Lamarche, Marie; Morais, José A (Obesity (Silver Spring, Md.), 2005)
OBJECTIVE: To compare the thermic response to a meal between men and women of varied body composition and to determine whether adrenergic amines extracted from citrus aurantium (CA) induce an increase in metabolic rate and enhance the thermic response to the meal. RESEARCH METHODS AND PROCEDURES: In 30 healthy weight-stable subjects (17 women, 13 men; BMI: 20 to 42 kg/m²), body composition was determined by bioimpedance analysis followed by resting energy expenditure for 20 minutes, and the thermic effect of food (TEF) of a 1.7-MJ, 30-gram protein meal was determined intermittently for 300 minutes by indirect calorimetry. In a subset of 22 subjects, the TEFs of CA alone and when added to the same 1.7-MJ meal were determined. Blood pressure and pulse before and throughout the studies and catecholamine excretion were determined. RESULTS: TEF was significantly lower in women than men (152 ± 7 vs. 190 ± 12 kJ and 8.8 ± 0.4% vs. 11.0 ± 0.7% of meal), independently of age and magnitude of adiposity. The thermic response to CA alone was higher in men, but, when added to the meal, CA increased TEF only in women and to values no longer different from men. CA had no effect on blood pressure and pulse rate but increased epinephrine excretion by 2.4-fold. DISCUSSION: A 20% lower TEF in women suggests a diminished sympathetic nervous system response to meals, because with CA, TEF increased by 29% only in women. However, this acute response may not translate into a chronic effect or a clinically significant weight loss over time.